Theoretical foundations of axion particles - Ezer, Cemile. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
The Standard Model of particle physics has solved the problem of giving masses to quarks and leptons by introducing the Higgs particle which soon will be searched at the Large Hadron Collider at CERN. Another problem of the Standard Model is the strong CP violation problem which arises due to the interplay between the strong and weak sectors of the model. An understanding of this problem requires understanding the instantons and the quark mixing. In this thesis I present my understanding of these topics and consider how the strong CP violation problem can be solved by introducing the axion particle.
Keywords: Higgs bosons.; Particles (Nuclear physics)